2011
DOI: 10.1111/j.1476-5381.2011.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution of Haemonchus contortus acetylcholine receptors in Xenopus oocytes provides mechanistic insights into levamisole resistance

Abstract: BACKGROUND AND PURPOSE The cholinergic agonist levamisole is widely used to treat parasitic nematode infestations. This anthelmintic drug paralyses worms by activating a class of levamisole‐sensitive acetylcholine receptors (L‐AChRs) expressed in nematode muscle cells. However, levamisole efficacy has been compromised by the emergence of drug‐resistant parasites, especially in gastrointestinal nematodes such as Haemonchus contortus. We report here the first functional reconstitution and pharmacological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
175
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(189 citation statements)
references
References 50 publications
9
175
2
3
Order By: Relevance
“…Polymorphism in b-tubulin isotype 1 seems to be most important for BZ resistance in H. contortus (Mottier and Prichard, 2008). Recently, our understanding of LEV resistance has greatly advanced with Boulin et al (2011) reporting that a number of changes in several genes, which together encode the acetylcholine receptor, result in loss of the LEV-sensitive acetylcholine receptor and thereby may cause resistance in veterinary nematodes. These data together with the findings of Kopp et al (2009) suggest that resistance to the nicotinic drugs is based on changes in the expression of the subunits that together form the receptor.…”
Section: Advances On the Molecular Basis Of Armentioning
confidence: 98%
“…Polymorphism in b-tubulin isotype 1 seems to be most important for BZ resistance in H. contortus (Mottier and Prichard, 2008). Recently, our understanding of LEV resistance has greatly advanced with Boulin et al (2011) reporting that a number of changes in several genes, which together encode the acetylcholine receptor, result in loss of the LEV-sensitive acetylcholine receptor and thereby may cause resistance in veterinary nematodes. These data together with the findings of Kopp et al (2009) suggest that resistance to the nicotinic drugs is based on changes in the expression of the subunits that together form the receptor.…”
Section: Advances On the Molecular Basis Of Armentioning
confidence: 98%
“…(D) A nicotine-sensitive, but levamisole-insensitive receptor is formed by expression of the C. elegans ACR-16 subunit (Raymond et al, 2000). (E) Omission of Hco-ACR-8 from the receptor shown in panel B results in a nAChR with reduced sensitivity to levamisole, but increased sensitivity to pyrantel (Boulin et al, 2011). (F).…”
Section: Neuromuscular Nachrmentioning
confidence: 97%
“…The H. contortus levamisole-sensitive receptor can be reconstituted in Xenopus oocytes by expressing the ACR-8, UNC-29, UNC-38 and UNC-63 subunits (Fig. 3) (Boulin et al, 2011). Removing the ACR-8 subunit from the H. contortus receptor produces a version which gives a smaller response to levamisole and acetylcholine, but is more sensitive to pyrantel, which is frequently thought to act at the same site at levamisole (Martin et al, 1991;Martin and Robertson, 2007).…”
Section: Neuromuscular Nachrmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies conducted on the pig nematode, Oesophagostomum dentatum, involving different members of this class including levamisole and pyrantel showed that there was a lower percentage of opened ionchannels in resistant worms compared to the counterparts, suggesting an increased desensitization of drug receptors in resistant isolates (Robertson et al, 1999(Robertson et al, , 2000. Neveu et al (2010) (Boulin et al, 2011). Further research showed that resistance to levamisole is associated with a spliced variant of the acr-8 gene, referred to as Hco-acr-8b which showed elevated expression in resistant worms and was undetectable in susceptible worms (Williamson et al, 2011).…”
Section: Specific Mechanisms Of Anthelmintic Resistancementioning
confidence: 99%